A Cerium-Based Nanocoating for Corrosion Protection of the AA1230 as Clad Material for the AA2024-T3 Alloy - Klumpp, Rafael Emil (2022)
Aluminum alloys are the state-of-art materials for structural components of aircrafts. As they are susceptible to localized corrosion, this kind of damage can become a major threat for its safe use in aircraft components. Therefore, surface protection of aluminum alloys against corrosion is a core issue in these applications. In this work, an alternative eco-friendly cerium-based surface pretreatment was developed and applied on the AA1230 clad of the AA2024-T3 alloy for corrosion protection. The corrosion resistance evaluation of this modified surface was evaluated by several techniques. The results were compared to chromium based conventional treatments and revealed that the coating layer, composed of spherical nodular nanostructures of cerium, obtained with the proposed eco-friendly treatment, improved the corrosion resistance of the alloy. Moreover, it was comparable to the corrosion behavior of chromate-treated alloy, showing that this treatment is a promising alternative to replace chromate based surface treatments.